(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2023)
The 1990s saw the emergence in Germany of the so-called “iconic turn” (ikonische Wende). Keith Moxey (2009) interprets this turn as a new paradigm that, fed up with the linguistic turn and the thesis of mediated access to reality, proposes the image as an instance of immediate access to the world, eliminating the distinction between subject and object. However, Boehm argues that the iconic turn must be understood on the basis of the turn of all turns, the Kantian transcendental turn. The hypothesis I will defend here is that the iconic turn is to be understood as a post-Kantian thought.